2008
DOI: 10.2337/dc07-1391
|View full text |Cite
|
Sign up to set email alerts
|

Can Self-Rated Health Scores Be Used for Risk Prediction in Patients With Type 2 Diabetes?

Abstract: OBJECTIVE -To investigate whether self-rated health profiles compiled using the EuroQol group's visual analog scale (EQ VAS) are independent predictors of vascular events and major complications in people with type 2 diabetes after controlling for standard clinical risk factors. RESEARCH DESIGN AND METHODS -The study is based on 7,348 individuals with a mean follow-up of 2.4 years after completing the EQ-5D questionnaire. We used Cox proportional hazards modeling to estimate hazard ratios associated with EQ VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 17 publications
(5 reference statements)
5
57
1
Order By: Relevance
“…In the present study, SRH was based on individuals’ assessment of their health status compared with that of peers their age. Similar to our results, SRH scores provide additional valuable information for risk prediction in patients with diabetes32, and it has also been recommended as a tool for assessing cardiovascular disease risk assessment33. Thus, diabetes guidelines should extend their focus on clinical and social aspects of diabetes to include questions on patient’s SRH34.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, SRH was based on individuals’ assessment of their health status compared with that of peers their age. Similar to our results, SRH scores provide additional valuable information for risk prediction in patients with diabetes32, and it has also been recommended as a tool for assessing cardiovascular disease risk assessment33. Thus, diabetes guidelines should extend their focus on clinical and social aspects of diabetes to include questions on patient’s SRH34.…”
Section: Discussionsupporting
confidence: 80%
“…Diabetes complications may be a confounder for SRH and glycemic control (Nielsen et al, 2011). Higher SRH measured by a visual analog scale was associated with lower risk of diabetes complications for a large New Zealand/Australian cohort (Hayes et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hayes and collegues reported that better HRQoL as assessed by the EQ-5D Visual Analog Scale was associated with a lower risk of diabetic complications and vascular events [19]. Kleefstra and colleagues also reported that the physical component summary of the RAND-36 was inversely associated with mortality in persons with type 2 diabetes [20].…”
Section: Discussionmentioning
confidence: 99%